2008
DOI: 10.1007/s10637-008-9140-5
|View full text |Cite
|
Sign up to set email alerts
|

Sulfinosine enhances doxorubicin efficacy through synergism and by reversing multidrug resistance in the human non-small cell lung carcinoma cell line (NCI-H460/R)

Abstract: A resistant non-small cell lung carcinoma cell line-NSCLC (NCI-H460/R) was established in order to investigate the potential of sulfinosine (SF) to overcome multidrug resistance (MDR). The cytotoxicity of doxorubicin (DOX) in NCI-H460/R cells was enhanced by interaction with SF. SF improved the sensitivity of resistant cells to DOX when NCI-H460/R cells were pretreated with SF. Synergism was accompanied by the accumulation of cells in S and G(2)/M phases. Pretreatment with SF was more potent in improving the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In a previous study, we showed that OA is also effective against MDR erythroleukemic cells overexpressing P-gp and its sensitive counterpart [24]. The present study was performed to examine the cytotoxic effects of OA on NSCLC cells (A549 and H460) that expressed both MRP1 [25], [26] and anti-apoptotic factors [7], [8], and to investigate the effects of this triterpene on pathways involved in drug resistance and the development of metastasis.…”
Section: Introductionmentioning
confidence: 93%
“…In a previous study, we showed that OA is also effective against MDR erythroleukemic cells overexpressing P-gp and its sensitive counterpart [24]. The present study was performed to examine the cytotoxic effects of OA on NSCLC cells (A549 and H460) that expressed both MRP1 [25], [26] and anti-apoptotic factors [7], [8], and to investigate the effects of this triterpene on pathways involved in drug resistance and the development of metastasis.…”
Section: Introductionmentioning
confidence: 93%
“…In the present study we examined the effects of combinations of DOX and two purine analogs, SF and 8-Cl-cAMP on human sensitive (NCI-H460) and MDR resistant (NCI-H460/R) LCNEC cell lines. SF promotes the reversion of DOX resistance in NCI-H460/R both alone [8] and in combination with curcumin [12]. Synergistically enhanced effects of SF and 8-Cl-cAMP were observed in the human neuroblastoma cell line [16].…”
Section: Discussionmentioning
confidence: 94%
“…The ready formation of adducts between SF and sulfhydryl compounds (glutathione and cysteine) is probably responsible for the observed lowering of glutathione levels by SF and subsequent induction of cell death. These findings have stimulated investigations of MDR reversal by SF in the LCNEC cell line [8,12].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations